The influence of consumption values on consumer satisfaction and repurchase intention in B2C and C2C e-commerce context - Xue, Jiao (My University, 2013)
In recent years, online shopping has emerged as an important retail channel option that accepted by more and more consumers. The development of e-commerce has brought tremendous opportunities but also fierce competitions for Internet retailers. In order to sustain commercial success, it is of vital importance for the Internet retailers to understand and cater the multi-dimensional consumption values sought by consumers, thereby creating more consumer satisfaction and maximizing online shoppers’ repurchase intention. It is the objective of this study to investigate the influence of consumption values on consumer satisfaction and repurchase intention in a B2C and C2C online shopping context by applying the TCV clarified by Sheth et al. (1991). Online survey was conducted to obtain empirical data used to test hypotheses. 73 qualified responses from European and 345 responses from Chinese were used for the analysis. The measurement model and structural model are tested applying SEM using Amos and SPSS. The results revealed that multi-dimensional consumption values had positive effects on consumer satisfaction and also affected repurchase intention directly or indirectly through the mediating effects of consumer satisfaction. Consumer satisfaction was tested positively affecting repurchase intention. These findings suggest that e-service providers should understand and deliver multi-dimensional consumption values to customers to make them feel satisfied which could in turn enhance consumer’s chance for repurchases and thereby realizing sustainable commercial success.
Keywords: Online shopping; consumption values; consumer satisfaction; repurchase intention; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|